Pengaruh Kepemimpinan Transformasional, Disiplin dan Motivasi Kerja terhadap Kinerja Guru - Fermi Enriko (Jurnal Pembangunan Nagari, 2018)
The study aims to determine how much Influence of Transformational Leadership, Discipline and Work Motivation on Teacher Performance MTsN 5 Padang. Study variables such as Transformational Leadership (X1), Discipline (X2), Work Motivation (X3) and Teacher Performance (Y) the data were collected by quisioner with 50 samples. The method of analysis used is multiple regression analysis. To test the hypothesis used t test and a significant F with 0,00 < 0,05 and Adjusted R Square (R²) 83,2%. The regression analysis showed that positive and significant influence of Transformational Leadership, Discipline and Work Motivation on Teacher Performance MTsN 5 Padang simultan cously or partially.